THE ROLE OF WALISONGO IN DEVELOPING THE ISLAM NUSANTARA CIVILIZATION - Abdurrohman Kasdi (ADDIN, 2017)
Walisongo is the most important stake in the history of Islamic deployment in Nusantara. Facts of the history show that after the propagation run by Walisongo, Islam grew rapidly and inspired the development of Islam Nusantara. The idea of Islam Nusantara came from the spirit of Walisongo’s Islam that later on continued by the scholars of Ahlussunnah wal Jama’ah with the mission of tolerant, peacefulness, open-minded, and accommodating with Nusantara culture. Understanding the formula of Islam Nusantara is very important to analyse the identity of Islam in Indonesia, using the process of selection, acculturation, and accommodation. The diverse of Islam Nusantara with the combination of three items (theology, fiqih, and tasawuf), have created diverse tradition which are consolidated, established and dominant since the age of Bintoro Demak Sultanate up to now.